Phase Formation during Solidification of Mg-Nd-Zn Alloys: An In Situ Synchrotron Radiation Diffraction Study - Tolnai, Domonkos (Materials (Basel), 2018)
Mg-4Nd base alloys with Zn additions of 3, 5 and 8 wt % were investigated with in situ synchrotron radiation diffraction during solidification. This method enabled the investigation of phase formation and transformation in the alloys. The diffraction results were supported with TEM observations on the as-solidified samples. The results show the effect of increased Zn addition on stabilizing the Mg(3)RE phase (RE—rare earth). The experimental results agree only partially with the theoretical calculations indicating the need to improve the existing thermodynamic database on the alloy system.